PUBLIC VALUE PENGGUNA MODA TRANSPORTASI BUS RAPID TRANSIT (BRT) KOTA SEMARANG - Aden Nurul Nuha; Retno Sunu Astuti; Yuliana Kristanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
In some developed countries, public transportation is the main choice for mobility, on the other hand, in Indonesia, most people still use private transportation, causing congestion. This condition indicates that the community has not fully utilized public transportation modes in carrying out activities. Public Value is a dialogue that is generated between the government in hearing a problem and to become a joint solution in improving an existing service based on the experience of the community and the needs of the community in using Trans Semarang. Using field observations and literature studies with a qualitative approach. Using public value theory, it was found that the reason for the lack of users and the increase in private vehicles was based on the poor experience of the community in using Trans Semarang and the unfulfillment of public value in services. Semarang as the basis for improvement and improvement of existing services.